Pressure Injury Surveillance and Prevention in Australia: Monash Partners Capacity Building Framework - Team, Victoria; Jones, Angela; Teede, Helena; Weller, Carolina D. (Frontiers in Public Health, 2021)
Hospital acquired pressure injury is a common complication across the globe. The severity of hospital acquired pressure injury ranges from skin redness and no skin breakdown to full skin and tissue loss, exposing tendons and bones. Hospital acquired pressure injury can significantly impact on quality of life. In addition to the human cost, hospital acquired pressure injury carries a high economic burden with the cost of treatment far outweighing preventative measures. Hospital acquired pressure injury rates are a key indicator of health services performance. Globally, health care services aim to reduce its incidence. In Australia, the federal health minister has prioritised the need for improvement in hospital acquired pressure injury surveillance and prevention. Capacity building is vital to optimise pressure injury surveillance and prevention in acute care services. In this perspective article, we provide a framework for capacity building to optimise hospital acquired pressure injury prevention and surveillance in a large cross-sector collaborative partnership in Australia. This framework comprises six key action areas in capacity building to optimise hospital acquired pressure injury outcomes, these include: research, organizational development, workforce development, leadership, collaboration, and consumer involvement.